2018
DOI: 10.1016/j.dental.2018.06.024
|View full text |Cite
|
Sign up to set email alerts
|

CAD-FEA modeling and analysis of different full crown monolithic restorations

Abstract: Materials with higher elastic modulus such as Co-Cr, zirconia and alumina enable higher tensile stress concentration on the crown intaglio surface and higher shear stress on the cement layer, facilitating crown debonding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
93
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 111 publications
(103 citation statements)
references
References 54 publications
9
93
1
Order By: Relevance
“…26 Some authors have reported that shear stress is the most prevalent stress on the cement layer, justifying the use of this in vitro test that evaluate this. 27 Thus, to overcome this limitations, we used a smaller adhesive area (2 mm 2 ), which gives more reliable results 4 . In addition, an orthodontic wire was used for the test with the aim of exerting a more uniform shear force on the adhesive interface.…”
Section: Discussionmentioning
confidence: 99%
“…26 Some authors have reported that shear stress is the most prevalent stress on the cement layer, justifying the use of this in vitro test that evaluate this. 27 Thus, to overcome this limitations, we used a smaller adhesive area (2 mm 2 ), which gives more reliable results 4 . In addition, an orthodontic wire was used for the test with the aim of exerting a more uniform shear force on the adhesive interface.…”
Section: Discussionmentioning
confidence: 99%
“…The incorporation of crystalline particles inside glasses matrices enables dental ceramics to reach high fracture resistance due to smaller crack propagations without compromising the final aesthetics (1). Among the main ceramics used in dentistry, lithium disilicate ceramics are noteworthy for their extensive indication: veneers, inlays, onlays (1), monolithic crowns (1,2), copings, fixed prostheses (1), hybrid abutments (3) and endocrowns (4). Another ceramic with a similar function is zirconia reinforced lithium silicate, possessing reinforcement crystals in the monosilicate phase instead of disilicate.…”
Section: Introductionmentioning
confidence: 99%
“…D ental ceramics are widely used in restorative treatments due to their excellent aesthetics, biocompatibility, and compressive strength [1]. Despite all the advances in ceramic material, the effects of tensile forces on restorations in function, especially in the posterior region [2][3][4][5], generate undesirable effects such as micro-cracks, delamination or catastrophic fractures due to the ceramic characteristic structures [6].…”
Section: Introductionmentioning
confidence: 99%
“…Some authors define that the multilayer arrangement provides early failure due to the incompatibility of materials with different mechanical properties [4]. Moreover, it is reported that, for multilayers design, the presence of a cement layer is responsible for absorbing part of the stress generated during loading [3] and reduces internal residual stress of polycrystalline ceramic system [4]. Thus, there is no data in the literature showing the biomechanical effect of a multilayer design of one glass ceramic system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation